Le problème territorial des Kouriles du Sud dans les relations nippo-soviétiques - Fistié, Pierre (Études internationales, 1982)
Since 1956 normal diplomatic relations have been re-established between Japon and Soviet Union, but without any peace treaty. That situation is linked to the problem of the Southern Kuriles occupied by USSR since 1945 but claimed by Japon which took possession of these islands at the end of the I8th century - a state of affairs recognized by Russia in 1855. The Yalta conference attributed « the Kuriles » to USSR and the Son Francisco Treaty (which Moscow did not sign) stipulated their relinquishment by Japon. The latter has always considered that tins text could not apply to the Southern Kuriles. The Hatoyamo government however was ready in 1955 to renounce the two main islands, but the same year the formation of the liberal-democrat party was accompanied by a sudden change in the Japanese position. The 1956 modus vivendi avoided the territorial question and mode possible the development of economic relations between the two countries but the Southern Kuriles problem was revived by Tokyo in the wake of the 1969 agreement on Okinawa. One finds it since at all the turning points of the nippo-soviet relations in spite of the fact that the re-establisment of diplomatic sino-japanese relations in 1972 and the acceptation of the anti-hegemony clause by Tokyo in 1978 make more unlikely than ever a solution in favour of Japan. This one, however, maintains its claim for reasons where the national psychology plays a great part while political and, above all, strategic motives render practically unthinkable that USSR will ever comply. The problem will remain as a thorn in the relations between Tokyo and Moscow.